Examination of internal training load parameters during the selection, preparation and competition phases of a mesocycle in elite field hockey players - Perrotta, A. S.; Held, N. J.; Warburton, D. E. R. (International Journal of Performance Analysis in Sport, 2017)
This investigation examined the magnitude of correlation between a global marker of exercise stress derived through ratings of perceived exertion (sRPE)- and a heart rate (HR)-derived training load during specific phases of a competitive mesocycle in elite field hockey players. Sixteen (n = 16) female field hockey players training as part of a national team were monitored over a six-week training block consisting of a player selection phase, a preparation phase and a competition phase. HR- and sRPE-derived training loads were recorded for each participant after on-field training sessions and international competition throughout the mesocycle. A significant correlation between sRPE- and HR-derived training loads was observed over the complete mesocycle [r = 0.83, 90% CL (0.77:0.88)]. The selection phase revealed a large correlation [r = 0.54, 90% CL (0.33:0.70], while a very large correlation was observed during the preparatory phase [r = 0.74, 90% CL (0.58:0.85)]. The competition phase revealed a moderate correlation over four international test matches [r = 0.48, 90% CL (0.05:0.70)]. This investigation sheds new light on the varying magnitude of correlation between sRPE- and an HR-derived training load during specific phases of a mesocycle in elite field hockey players training within a national team.